Towards building a diving simulator for organizing dives in real conditions - Aristidou, Kalia; Michael-Grigoriou, Despina (My University, 2014)
We present a prototype of a diving simulator system that can be used for organizing dives in real conditions. Our simulator comprises of (a) an accurate visualization of a real wreck site in Mediterranean sea, Zenobia Cyprus, one of the most well-known wrecks worldwide and (b) visualization of marine life based on the real types of species that are gathering near the wreck. Moreover, a first attempt of integrating an existing diving computation algorithm has been made. The simulator's purpose, in its complete framework, is to be used by divers to organize their dives in advance at the specific wreck and moreover to be used as a tool to promote diving tourism. The diving computation part of the simulator has been validated according to the Professional Association of Diving Instructor's data, while the complete prototype of the system has been evaluated by expert users (divers) denoting the importance of the specific simulator.
Keywords: Dive computations; Diving simulator; Diving tourism; Marine life